2020
DOI: 10.1038/s41598-020-73848-w
|View full text |Cite
|
Sign up to set email alerts
|

ZIF-8 as a promising drug delivery system for benznidazole: development, characterization, in vitro dialysis release and cytotoxicity

Abstract: Chagas disease (CD), caused by the flagellate protozoan Trypanosoma cruzi, is one of the major public health problems in developing countries. Benznidazole (BNZ) is the only drug available for CD treatment in most countries, however, it presents high toxicity and low bioavailability. To address these problems this study used Zeolitic Imidazolate Framework-8 (ZIF-8), which has garnered considerable attention due to its potential applications, enabling the controlled delivery of drugs. The present work developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…Although the lung is not a hemopoietic organ, it is also involved in the formation of platelets. 18 Last, the kidney generates erythropoietin (EPO) which acts on the bone marrow hematopoietic system to promote the differentiation and maturation of pronormoblasts, facilitate the uptake and utilization of Fe in bone marrow, accelerate the generation of hemoglobin and erythrocyte, and promote the release of bone marrow reticulocytes into blood. 37 As mentioned above, therefore, it is necessary to make intensive research on the effect of ZIF-8 MOFs on these tissues and organs when they enter the blood, and to make further evaluation of blood compatibility of ZIF-8 MOFs in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the lung is not a hemopoietic organ, it is also involved in the formation of platelets. 18 Last, the kidney generates erythropoietin (EPO) which acts on the bone marrow hematopoietic system to promote the differentiation and maturation of pronormoblasts, facilitate the uptake and utilization of Fe in bone marrow, accelerate the generation of hemoglobin and erythrocyte, and promote the release of bone marrow reticulocytes into blood. 37 As mentioned above, therefore, it is necessary to make intensive research on the effect of ZIF-8 MOFs on these tissues and organs when they enter the blood, and to make further evaluation of blood compatibility of ZIF-8 MOFs in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the existing knowledge on the biocompatibility of the ZIF-8 MOFs is not consistent. [15][16][17][18][19] For example, Vasconcelos et al did not found signicant cytotoxicity of the ZIF-8 MOF crystals loading an anti-cancer drug (doxorubicin) towards three cell lines (NCI-H292; HT-29; and HL-60). 20 However, Tamames-Tabar et al 16 observed that the half maximum inhibitory concentrations (IC50) of ZIF-8 MOF on HeLa and J774 cells were 100 and 25 mg mL À1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the material characterization are consistent with several previous studies. [48][49][50] Degradation of ZIF-8 in water, PBS, and 0.9% saline solutions…”
Section: Synthesis and Characterisation Of Zif-8 Crystalsmentioning
confidence: 99%
“…18,22 The XRD pattern recorded for ZIF-8 demonstrated high crystallinity as judged by its diffraction pattern with characteristic sharp peaks at 2θ = 7.17°, 10.2°, 12.67°and 17.8°. 23 The isolated MOFs demonstrated permanent microporosity as shown from the corresponding N 2 sorption isotherms, Fig. 1c.…”
Section: Synthesis and Characterization Of The Different Zr-and Zn-ba...mentioning
confidence: 83%